2021
DOI: 10.1371/journal.pone.0250254
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel non-invasive biological marker to overcome the shortcomings of PSA in diagnosis and risk stratification for prostate cancer: Initial prospective study of developmental endothelial locus-1 protein

Abstract: Objective This prospective study sought to clarify the developmental endothelial locus-1 (Del-1) protein as values of diagnosis and risk stratification of prostate cancer (PCa). Design From February 2017 to December 2019, a total 458 patients who underwent transrectal ultrasound guided prostate biopsy or surgery of benign prostatic hyperplasia agreed to research of Del-1 protein. We prospectively compared and analyzed the Del-1 protein and prostate specific antigen (PSA) in relation to the patients’ demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Another study showed that FABP5 distinguished between healthy individuals and patients with low-risk (GS 6) and intermediate–high-risk PCa tumours [ 193 ]. The EV levels of PTEN [ 194 ], flotillin 2 and PARK7 [ 195 ], ephrinA2 [ 196 ], Del-1 [ 197 ], the integrins ITGA3 and ITGB1 [ 198 ] and GGT1 activity [ 199 ] have also been reported to differentiate between PCa patients and healthy individuals and/or BPH patients. In addition, the prostate-enriched protein STEAP1 was found to be increased in plasma samples of PCa patients compared with healthy males [ 200 ].…”
Section: Ev-based Biomarkers For Prostate Cancermentioning
confidence: 99%
“…Another study showed that FABP5 distinguished between healthy individuals and patients with low-risk (GS 6) and intermediate–high-risk PCa tumours [ 193 ]. The EV levels of PTEN [ 194 ], flotillin 2 and PARK7 [ 195 ], ephrinA2 [ 196 ], Del-1 [ 197 ], the integrins ITGA3 and ITGB1 [ 198 ] and GGT1 activity [ 199 ] have also been reported to differentiate between PCa patients and healthy individuals and/or BPH patients. In addition, the prostate-enriched protein STEAP1 was found to be increased in plasma samples of PCa patients compared with healthy males [ 200 ].…”
Section: Ev-based Biomarkers For Prostate Cancermentioning
confidence: 99%
“…Despite a lower incidence rate among Asians compared to Americans and Europeans ( 1 ), the mortality and morbidity rates associated with PCa are on the rise in China due to improvements in living standards, lifestyle changes, and advancements in screening methods ( 2 , 3 ). The use of prostate-specific antigen (PSA) for population screening, diagnosis, and monitoring of PCa has been a subject of controversy since its purification ( 4 ). Although PSA screening has some benefits, such as early detection of PCa, it also has several drawbacks, such as high costs, long waiting times, limited sensitivity, and low specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have illuminated significant variances in the approach toward the evaluation and management of hematuria among male and female patients. Efforts are currently underway to standardize evaluation processes and develop comprehensive risk stratification models, with the goal of providing equitable, unbiased, and evidence-based care to all patients, irrespective of gender [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%